Oral Health Problems of Children with Cancer After Chemotherapy: A Literature Review - Naviati, Elsa; Afiyanti, Yati; Allenidekania, Allenidekania; Nugroho, Agus (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Pediatric cancer patients are particularly vulnerable to oral health complications, primarily due to the adverse effects of chemotherapy. This treatment significantly influences both oral health and nutritional status, especially in children diagnosed with acute lymphoblastic leukemia (ALL). Chemotherapy can trigger a range of oral issues, including mucositis, dry mouth (xerostomia), and oral infections, which in turn can hinder proper nutritional intake and compromise overall health. This paper aims to investigate the impact of chemotherapy on oral health and nutrition in pediatric cancer patients, focusing on those with ALL. Through a literature review, the study examines the prevalence and types of oral complications and their effects on well-being. Relevant literature published between 2014 and 2024 was sourced from databases such as EBSCO, ScienceDirect, SpringerLink, ProQuest, and Scopus. Using the PICO (Population, Intervention, Comparison, and Outcomes) framework, articles were selected and critically appraised by two independent reviewers. A descriptive method was employed to analyze the data. Out of 2,465 initially identified articles, eight were selected for in-depth analysis. The findings show that pediatric cancer patients face both immediate and long-term oral health issues, including dental abnormalities and jaw development problems. These complications can cause pain, eating difficulties, and social stigma, negatively affecting the child's quality of life. The study emphasizes the need for early oral health intervention, better training for healthcare providers, and the development of standardized oral care protocols. Future research should aim to assess the effectiveness of targeted oral health interventions in improving nutrition and overall quality of life in pediatric oncology patients.